Albania : Staff Report for the 2000 Article IV Consultation and Second Review Under the Second Annual Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2000)
The Kosovo crisis in March 1999 and the large influx of refugees placed a considerable strain on the country. Progress in structural reforms has been significant considering the Kosovo crisis. The process of privatizing about 520 small and medium-size enterprises was completed, contracts were signed for the transfer of copper and chromium mines to foreign investors, and albeit with delay, the authorities' recently signed agreement with investors on the privatization of the National Commercial Bank. Executive Directors commended the Albanian authorities for their policies to maintain macroeconomic stability.